Abnormal Arm Tone, Cigarette Smoking and Use of Blood Pressure Medication in a Sight Enhancement Clinic Population - Paetkau, M.E (Canadian Journal of Optometry, 2021)
There are three pigmented tissues originating from neural crest which frequently degenerate during aging in industrialized societies: the pigmented epithelium of the eye, the substancia nigra of the thalmus and the pigmented cells of the organ of Corti. Each of these tissues once developed does not regenerate following loss. They must last the insults of a lifetime for the elderly to see clearly, hear well, and have smooth coordination. Is degeneration of these tissues interrelated? Are they influenced by common risk factors?